2005
DOI: 10.1080/10611860400024110
|View full text |Cite
|
Sign up to set email alerts
|

In vivoevidence for the efflux transport of pentazocine from the brain across the blood–brain barrier using the brain efflux index method

Abstract: The efflux transport of pentazocine (PTZ) from the brain across the blood-brain barrier (BBB) was investigated using the Brain Efflux Index method. PTZ was eliminated with the apparent elimination half-life of 13.0 min after microinjection into the parietal cortex area 2 region of the rat brain. The apparent efflux clearance of PTZ across the BBB was 137 microl/min/g brain, which was calculated from the elimination rate constant (5.35 x 10(-2) min(-1) and the distribution volume in the brain (2.56 ml/g brain).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 31 publications
(29 reference statements)
4
14
0
Order By: Relevance
“…By contrast, there is very little available information about the efflux transport at the BBB concerning the opioid agonist/antagonist analgesics that may be affected by Pgp. Recently, we demonstrated by in vivo approaches that the penetration of pentazocine into the rat brain is restricted by P-gp-mediated efflux (Moriki et al 2004(Moriki et al , 2005, which is consistent with a previous observation in in vitro multidrug resistant cells (Callaghan and Riordan 1993). In order to predict clinically the relevant interactions with P-gp substrates, it is of great importance to clarify the involvement of P-gp in the BBB transport of opioid-related analgesics.…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…By contrast, there is very little available information about the efflux transport at the BBB concerning the opioid agonist/antagonist analgesics that may be affected by Pgp. Recently, we demonstrated by in vivo approaches that the penetration of pentazocine into the rat brain is restricted by P-gp-mediated efflux (Moriki et al 2004(Moriki et al , 2005, which is consistent with a previous observation in in vitro multidrug resistant cells (Callaghan and Riordan 1993). In order to predict clinically the relevant interactions with P-gp substrates, it is of great importance to clarify the involvement of P-gp in the BBB transport of opioid-related analgesics.…”
Section: Introductionsupporting
confidence: 74%
“…Unlabeled typical P-gp inhibitor, the same as described above, was dissolved in the ECF buffer at pH 7.4 to yield the final concentrations. To examine the dose-dependent effect of unlabeled verapamil, injection solution at the high concentration (4.0 mM) of verapamil was adjusted at pH 7.2 to be dissolved, as described previously (Kusuhara et al 1997;Moriki et al 2005). After microinjection of drug into the cerebrum, aliquots of cerebrospinal fluid (CSF) were collected from the cisterna magma at appropriate times, as reported previously (Kakee et al 1996).…”
Section: Determination Of Bui Into the Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…By semilogarithmic fitting of the (100 -BEI)-values versus time, the apparent efflux rate constant from the brain (k eff ) is obtained, which is necessary to determine the apparent brain efflux clearance (Cl eff [l 3 t -1 ] (Isakovic et al 2004;Moriki et al 2005;Raybon and Boje 2001;Terasaki 1999):…”
Section: In Situ Brain Perfusionmentioning
confidence: 99%
“…As noted previously, there is evidence for a cationic carrier-mediated influx system for pentazocine, DPHM, and other cationic substances (Suzuki et al, 2002a,b). Moriki et al (2005) have provided evidence that P-glycoprotein acts as BBB efflux transporter for this compound. However, DPHM is not a P-glycoprotein substrate (Chen et al, 2003), although we have previously shown that propranolol, which inhibits P-glycoprotein (Bachmakov et al, 2006), significantly increases the brain/plasma ratios of DPHM in adult sheep (Au-Yeung et al, 2006).…”
Section: Discussionmentioning
confidence: 99%